Madurez Vocacional en Estudiantes de Primer Semestre de la Facultad de Psicologia - Universidad Antonio Nariiio - Sede Riohacha del departamento de La Guajira - Colombia. - Romero Suarez, Mayerlis Andrea (Universidad Antonio Nariño, 2021)
The objective of this research is to evaluate the level of vocational maturity of first semester students of the Faculty of Psychology - Antonio Narino University- Riohacha campus of the department of La Guajira - Colombia. For this, we worked with a quantitative method, with a descriptive scope, where an instrument (IMV) was applied that in turn evaluated the level of maturity in a genera l and specific way in each of the five dimensions that the theory shows, counting on a sample of 25 students from the faculty of psychology at the Antonio Narino University - Riohacha campus of the Department of La Guajira- Colombia.